Liquid crystalline behavior and photoluminescence of lanthanide decanoate nanoparticles synthesized by microwave radiation. Issue 15 (29th March 2021) - Davis-Wheeler Chin, Clare; Lee, Harold O.; Griego, James J. M.; Treadwell, LaRico J.
Abstract : Luminescent lanthanide decanoate nanoparticles (LnC10 NPs; Ln = Pr, Nd, Sm, Eu, Gd, Er) with spherical morphology (<100 nm) have been synthesized via a facile microwave (MWV) method using Ln(NO3 )3 · x H2 O, ethanol/water, and decanoic acid. Abstract : Luminescent lanthanide decanoate nanoparticles (LnC10 NPs; Ln = Pr, Nd, Sm, Eu, Gd, Er) with spherical morphology (<100 nm) have been synthesized via a facile microwave (MWV) method using Ln(NO3 )3 · x H2 O, ethanol/water, and decanoic acid. These hybrid nanomaterials adopt a lamellar structure consisting of inorganic Ln 3+ layers separated by a decanoate anion bilayer and exhibit liquid crystalline (LC) phases during melting. The particle size, crystalline structure, and LC behavior were characterized using transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and powder X-ray diffraction (ambient and heated). Thermal analysis indicated the formation of Smectic A LC phases by LnC10 nanoparticles, with the smaller lanthanides (Ln = Sm, Gd, Er) displaying additional solid intermediate and Smectic C phases. The formation of LC phases by the smaller Ln 3+ suggests that these nanoscale materials have vastly different thermal properties than their bulk counterparts, which do not exhibit LC behavior. Photoluminescence spectroscopy revealed the LnC10 NPs to be highly optically active, producing strong visible emissions that corresponded to expected electronic transitions by the various Ln 3+ ions. Under long-wave UV irradiation ( λ = 365 nm), bright visible luminescence was observed for colloidal suspensions of Nd, Sm, Eu, Gd, and ErC10 NPs. To the best of the authors' knowledge, this is the first reported synthesis of nanoscale metal alkanoates, the first report of liquid crystalline behavior by any decanoate of lanthanides smaller than Nd, and the first observation of strong visible luminescence by non-vitrified lanthanide alkanoates.